Examining the dimensionality, reliability, and invariance of the Chinese version of the Resilience Scale-14: A multicenter cross-sectional survey in Chinese junior nurses - Zhao, Weidong; Shu, Ting; Ma, Yue; Wei, Xuemei; Zhu, Cairong; Peng, Liping; Zhao, Lihong; Zhang, Qin (Frontiers in Psychiatry, 2022)
Background This study aimed to present the psychometric properties (dimensionality, reliability, and invariance) of the Chinese 14-Item Resilience Scale (RS-14) within Chinese register nurses (RNs) with less than 3 years work experiences. And we aimed to compare the fit of a unidimensional model and a bifactor model. Materials and methods This multicenter cross-sectional survey was conducted from August to September in 2019. A total of 7,231 registered nurses from 90 hospitals were recruited. Data was anonymously obtained through online questionnaires. Both reliability and validity of Chinese RS-14 were assessed. The confirmatory factor analyses (CFA) were used to compare the fit of two different factor structures of the RS-14 (unidimensional model vs. a bifactor model). Moreover, multigroup CFA (MGCFA) were applied to evaluate the measurement invariance (MI) across sociodemographic parameters (gender, educational level, marital status, and et al.). Design Cross-sectional quantitative analyses. Results Our study confirmed that the bifactor model presented the best fit within Chinese nurses (CFI = 0.924, TLI = 0.909, RMSEA = 0.095, SRMR = 0.043), and found strong factorial invariance across gender, marital status, and status of receiving standardized training. The reliability of RS-14 was high with a Cronbach’s alpha coefficient of 0.939. Moreover, RS-14 was positively correlated with the social support and was negatively correlated with workplace bullying. Conclusion This is the first study to explore the latent factor structure for the RS-14 among Chinese RNs and evaluated MI across a series of sociodemographic variables. Based on our findings, the Chinese version RS-14 is both valid and reliable.